2018
DOI: 10.1088/1361-648x/aabeb5
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting selenides intercalated with organic molecules: synthesis, crystal structure, electric and magnetic properties, superconducting properties, and phase separation in iron based-chalcogenides and hybrid organic-inorganic superconductors

Abstract: Layered iron-based superconducting chalcogenides intercalated with molecular species are the subject of intensive studies, especially in the field of solid state chemistry and condensed matter physics, because of their intriguing chemistry and tunable electric and magnetic properties. Considerable progress in the research, revealing superconducting inorganic-organic hybrid materials with transition temperatures to superconducting state, T , up to 46 K, has been brought in recent years. These novel materials ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 236 publications
1
9
0
Order By: Relevance
“…Clarke et al reported the first reliable crystal structure determination of Li-ammonia intercalate in FeSe with T c as high as 43 K, as well as in situ characterization of the reactions of Li/NH 3 with FeSe using X-ray and neutron diffraction . Insertion of transition metal coordination complexes with bulky ligands between the Fe chalcogenide layers allows further expansion of the interlayer space , and contributes in tuning interactions of Fe-amine complexes with chalcogenide fragments. Ethylenediamine ( en ) has been widely used as both a bidentate ligand and a solvent in the synthesis of such materials due to its versatility, high tendency to coordinate with transition metals, and compatibility with Fe-based chalcogenides. …”
Section: Introductionmentioning
confidence: 99%
“…Clarke et al reported the first reliable crystal structure determination of Li-ammonia intercalate in FeSe with T c as high as 43 K, as well as in situ characterization of the reactions of Li/NH 3 with FeSe using X-ray and neutron diffraction . Insertion of transition metal coordination complexes with bulky ligands between the Fe chalcogenide layers allows further expansion of the interlayer space , and contributes in tuning interactions of Fe-amine complexes with chalcogenide fragments. Ethylenediamine ( en ) has been widely used as both a bidentate ligand and a solvent in the synthesis of such materials due to its versatility, high tendency to coordinate with transition metals, and compatibility with Fe-based chalcogenides. …”
Section: Introductionmentioning
confidence: 99%
“…Except simple metal cations, solvates of selected alkali or alkaline-earth metals with bases (cf. ammonia, aliphatic amines, diamines, and aromatic amines) comprise another type of intercalating species that can enter the structure of β-FeSe as electron donors that further promote T c enhancement . Interestingly, in these types of iron chalcogenide intercalates, there is a correlation of the interlayer spacing ( d , defined as the Fe–sheet distance in adjacent FeSe layers, along the c axis) with T c , which empirically shows a progressive growth of T c with increasing d that saturates at a separation of d ∼ 8.6 Å .…”
Section: Introductionmentioning
confidence: 99%
“…22 However, intercalation reactions with β-FeSe as host compound can proceed at low temperatures via soft chemistry methods. [23][24][25][26][27] Examples are the intercalation of lithium ions together with amine and amide species in liquid ammonia (Li x (NH 2 ) y (NH 3 ) 1−y Fe 2 Se 2 , T c = 43 K), 28 of lithium hydroxide layers ([(Li 1-x Fe x )OH]FeSe, T c = 42 K) 29 by hydrothermal methods, or of alkaline ions with amine molecules (Na 0.39 (C 2 N 2 H 8 ) 0.77 Fe 2 Se 2 T c = 46 K) by solvothermal reactions. 26 Another promising approach is the electrochemical intercalation of alkali metal ions.…”
mentioning
confidence: 99%
“…However, intercalation reactions with β-FeSe as host compound can proceed at low temperatures via soft chemistry methods. Examples are the intercalation of lithium ions with amine and amide species in liquid ammonia (Li x (NH 2 ) y (NH 3 ) 1– y Fe 2 Se 2 , T c = 43 K), lithium hydroxide layers by hydrothermal methods ([(Li 1– x Fe x )­OH]­FeSe, T c = 42 K), or alkaline ions with amine molecules by solvothermal reactions (Na 0.39 (C 2 N 2 H 8 ) 0.77 Fe 2 Se 2 , T c = 46 K) …”
mentioning
confidence: 99%